Moving Mesh Kinetic Simulation for Sheared Rodlike Polymers with High Potential Intensities (Communications in Computational Physics, 2006)
The Doi-Hess equation that describes the evolution of an orientational distribution function is capable of predicting several rheological features of nematic polymers. Since the orientational distribution function becomes sharply peaked as potential intensity increases, powerful numerical methods become necessary in the relevant numerical simulations. In this paper, a numerical scheme based on the moving grid techniques will be designed to solve the orientational distribution functions with high potential intensities. Numerical experiments are carried out to demonstrate the effectiveness and robustness of the proposed scheme.